2022
DOI: 10.1088/2053-1583/ac9dab
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic laser-pulse-induced magnetization dynamics in van der Waals magnet Fe3GeTe2

Abstract: Femtosecond laser-pulse excitation provides an energy efficient and fast way to control magnetization at the nanoscale, providing great potential for ultrafast next-generation data manipulation and nonvolatile storage devices. Ferromagnetic van der Waals materials have garnered much attention over the past few years due to their low dimensionality, excellent magnetic properties, and large response to external stimuli. Nonetheless, their behaviour upon fs laser-pulse excitation remains largely unexplored. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…50−55 The ultrafast magnetization dynamics can reveal important spinrelated effects including electron−electron and spin−phonon interactions. 56−62 Progress has been achieved recently in understanding the ultrafast magnetization process in few-layer flakes of vdW magnetic materials, e.g., CrI 3, 63,64 Fe 3 GeTe 2, 65 and Gr 2 Ge 2 Te 6. 66,67 However, ultrafast dynamics of magnetization of monolayer 2D magnets has not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…50−55 The ultrafast magnetization dynamics can reveal important spinrelated effects including electron−electron and spin−phonon interactions. 56−62 Progress has been achieved recently in understanding the ultrafast magnetization process in few-layer flakes of vdW magnetic materials, e.g., CrI 3, 63,64 Fe 3 GeTe 2, 65 and Gr 2 Ge 2 Te 6. 66,67 However, ultrafast dynamics of magnetization of monolayer 2D magnets has not been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrafast magnetization dynamics in 2D vdW magnets has attracted significant attention due to its potential applications in ultrafast information technology and fundamental physics. The ultrafast magnetization dynamics can reveal important spin-related effects including electron–electron and spin–phonon interactions. Progress has been achieved recently in understanding the ultrafast magnetization process in few-layer flakes of vdW magnetic materials, e.g., CrI 3, , Fe 3 GeTe 2, and Gr 2 Ge 2 Te 6. , However, ultrafast dynamics of magnetization of monolayer 2D magnets has not been reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This demagnetization is attributed to a transfer of heat from the hot electrons to the magnons, whose excitation reduces the F3GT average magnetization. Longitudinal demagnetization effects like Stoner excitations are still possible, but it has been shown that in metallic systems their effect is secondary with respect to magnons 63 and a recent study has proved a magnon+Elliot-Yafet picture for the F3GT demagnetization 70 .…”
Section: Low Temperature Measurementsmentioning
confidence: 99%
“…Nevertheless, the use of light probes such ultrafast laser pulses to generate and manipulate topological spin textures on 2D vdW compounds is currently unknown. There have been recent reports on pump probe measurements on 2D magnets [42][43][44] , but the demonstration of the formation of spin textures via ultrafast laser excitations is yet to be reported.…”
Section: Introductionmentioning
confidence: 99%